Spatio-Temporal Assessment of the Shrinking Lake Burdur, Turkey - Dervisoglu, Adalet; Yağmur, Nur; Firatli, Ertug; Musaoglu, Nebıye; Tanık, Aysegul (My University, 2022)
Water resources in the world are becoming scarce due to both natural climatic conditions under the effect of climate change and human-induced activities. The population is rising day-by-day leading to a steady decrease in water resources, which in turn, highly disturbs the natural ecological functions of the vulnerable systems. Lakes can be addressed as important water bodies that are under the effect of shrinkage in different parts of the world, and if no remedial measures are taken, they will disappear in the near future. Lake Burdur in Turkey is among such lakes that lose its water volume over time. This study was performed via a group of interdisciplinary scientists to analyze the spatial and temporal changes in the water surface area in the long-term (1985-2020) and in the short-term (2016-2020) with the aim of putting forth the areal changes. Remote sensing technology was utilized for this purpose. Landsat imagery and Sentinel 2 images were utilized for the long and short-term assessments, respectively. Meteorological conditions during the inspection terms were obtained from the State Meteorological Service to determine the dominating reason(s) of area changes over time. Natural conditions and anthropogenic activities are linked with the findings. Resultantly, water withdrawals from the dams and reservoirs built in the region and from the streams feeding the lake for irrigation purposes during the dry season represent the human-induced activities dominate over the natural causes of climate change as is the case in most of the water bodies of the world. This outcome was also confirmed by a detailed analysis of the agricultural areas in the basin through satellite images and by field trips made at the site.
Keywords: Landsat; NDWI; Sentinel 2; Burdur Lake; Change Analysis; Anthropogenic Activities; Natural Conditions